The DOG 1 EXPRESSION IN DIFFERENTIAL DIAGNOSIS OF CHONDROBLASTOMAS AND ITS HISTOLOGICAL MIMICKERS - Maryam Nisar (Army Medical College Rawalpindi, 2020)
Objective: Chondroblastoma is rare benign cartilage forming tumor of bone predominantly in individuals less than 20 years of age. Recently immunohistochemical marker DOG 1 has been reported to help in the diagnosis in difficult cases where histological features overlap with other similar entities. Current study aims to assess the sensitivity and specificity of DOG 1 in the diagnosis of chondroblastomas.